Drought and the farming sector: Loss of farm animals and post-drought rehabilitation - Toulmin, C. (International Livestock Centre for Africa, 1986)
Outlines the main effects of drought on crop producers and examines the effects of drought on crop producers and examines the effects of drought induced livestock losses on crop production and considers a range of policy measures aimed at rehabilitation of the farm sector in the post-drought period; compares alternative policy measures.